2016
DOI: 10.1590/s1678-9946201658058
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epstein-Barr Virus (Ebv) but Not Human Papillomavirus (Hpv) With Gingivitis and/or Periodontitis in Transplanted Individuals

Abstract: SUMMARYThe aim of this study was to investigate the association of EBV and HPV with gingivitis and/or periodontitis according to the immunologic status. To this end, 74 oral biopsies from transplanted and non-transplanted individuals with the abovementioned oral manifestations were submitted to a screening by PCR for both viruses. According to the results, EBV was strongly associated with gingivitis and/or periodontitis in transplanted individuals (p = 0.011) but not HPV (p = 0.766). EBV-HPV co-detections did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Since the study carried out by the Hospital Alemán was based on the Sabin Feldman Dye Test, a more sensitive test than the one used in the present work, this could not account for the difference observed. A possible explanation is that Chascomús is a rural area which was demonstrated to be a risk factor for T. gondii infection as observed by others (Rostami et al., 2016) (Wilking et al., 2016). In the city of Chascomús only part of the individuals are linked to rural activities, independent of the area where they live, and it could be observed that the seroprevalence among people with farm or rural activities in comparison with individuals that never had any relationship with rural activities was not significantly different (Table 2).…”
Section: Resultsmentioning
confidence: 69%
“…Since the study carried out by the Hospital Alemán was based on the Sabin Feldman Dye Test, a more sensitive test than the one used in the present work, this could not account for the difference observed. A possible explanation is that Chascomús is a rural area which was demonstrated to be a risk factor for T. gondii infection as observed by others (Rostami et al., 2016) (Wilking et al., 2016). In the city of Chascomús only part of the individuals are linked to rural activities, independent of the area where they live, and it could be observed that the seroprevalence among people with farm or rural activities in comparison with individuals that never had any relationship with rural activities was not significantly different (Table 2).…”
Section: Resultsmentioning
confidence: 69%
“…Periodontal immunity includes overlapping innate and adaptive cellular and humoral responses , which, together with indigenous oral microbes , aim at controlling invading pathogens. In turn, periodontopathic bacteria and herpesviruses in marginal periodontitis (recent publications: ) and apical periodontitis (recent publications: ) elaborate a variety of defense mechanisms to circumvent or disrupt protective host immune reactions .…”
Section: The Struggle Between Periodontal Microbes and Immunitymentioning
confidence: 99%
“…EBV and CMV often co-exist in marginal and apical periodontitis. A recent study reported that EBV could induce gingivitis and/or periodontitis in an immune permissive environment, such as in organ transplanted patients 19 . Oral hairy leukoplakia (OHL) is a disease of the mucosa associated with EBV infection and developing mostly in HIV infected patients, as well as in HIV-negative patients with organ transplants or immunocompromising diseases.…”
Section: Enanthems Associated With Viral Infectionsmentioning
confidence: 99%